Stress, Spirituality, and Altruism of Brazilian Medical Students during the COVID-19 Pandemic: A Cross-sectional Analysis (Research, Society and Development, 2022)
Spirituality and altruism may be critical coping strategies to minimize emotional pain during period of crisis. Here we aim to investigate how spirituality and altruism are related and whether they influence medical students' levels of stress during the COVID-19 pandemic. Data were collected when most Brazilian states had already been promoting social isolation in response to the COVID-19 pandemic using self-reported measures: the Perceived Stress Scale 4, the Self-Spirituality Rating Scale, and Altruistic Attitudes Scale, in an online questionnaire.  We found moderate levels of perceived stress, moderate to high levels spirituality, as well as high levels of altruistic attitudes. Reported stress was higher among participants with a previous diagnosis of mental disorder and women, while more altruistic individuals were less vulnerable to it. Most participants attributed their stress symptoms to the COVID-19 pandemic or to the social isolation and participants with higher level of stress were less able to study during the pandemic. Spirituality correlated positively with altruistic thoughts and emotions, but only participants who act altruistically reported lower levels of stress. Our results indicate that the mental health status before the COVID-19 pandemic is related to the actual level of stress and suggest that altruism may allow for collective coping of emotional burden during the health crisis.